International education governance in the francophone microcosm - Le Mouillour, Isabelle [Verfasser] (My University, 2021)
"International cooperation is high on the agenda of policy makers in times of globalisation and shared challenges such as climate change, poverty, equity or digitalisation. The present paper investigates strategies and actors involved in international cooperation policy in the field of vocational education and training within the francophone area. Using a discursive institutionalism approach as an analysis frame, the article traces and identifies the development of ideas and discourses. It also examines the changes and tensions in the French public institutional set-up in that specific policy field. The analysis builds on analysis of policy documents, mission statements of actors involved (ministries, public and private actors, non-for-profit organisations, international and European actors)." (Author's abstract, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 2.2.1 Westeuropa; 370; Berufsbildung; Internationale Zusammenarbeit; Institutionalismus; Frankreich